CONSIDERATIONS FOR MEASURING GROUND CO2 EFFLUXES WITH CHAMBERS - Welles J.M.; Demetriades-Shah T.H.; McDermitt D.K. (My University, 2001)
This paper considers the factors that influence ground CO2 fluxes as measured by the chamber method. New data and published results are used to illustrate the effects of various factors on CO2 emissions from the ground. These factors are: pressure differences between the ambient air and the chamber, wind speed within the chamber, the chamber CO2 concentration relative to ambient air concentration and the accumulation of water vapor in the chamber. A mathematical analysis of the accumulation of CO2 in the chamber in terms of diffusion and advection (e.g., air flow out of the ground at geothermal degassing locations) shows that the same protocol should be followed, whether the mechanism of emission is purely by diffusion or by a combination of diffusion and advection. The analysis also yields a simple way for estimating soil CO2 conductance and the soil CO2 concentration at the depth of insertion of the chamber into the ground.
Keywords: CARBON DIOXIDE; FLUX; RESPIRATION; SOIL GASES